Evaluation of transfection efficacy, biodistribution, and toxicity of branched amphiphilic peptide capsules (BAPCs) associated with mRNA. (18th October 2022) - Kunte, Nitish; Westerfield, Matthew; McGraw, Erin; Choi, Jiyeong; Akinsipe, Tosin; Whitaker, Susan K.; Brannen, Andrew; Panizzi, Peter; Tomich, John M.; Avila, L. Adriana
Abstract : BAPCs are PEG free nanoparticles with potential to deliver therapeutic mRNA in vivo . Association of mRNA with BAPCs surface enhanced localization in lung by avoiding liver and spleen. Therefore, potentiating their application in lung therapy. Abstract : Nanoparticles (NPs) have been shown to be a suitable mRNA delivery platform by conferring protection against ribonucleases and facilitating cellular uptake. Several NPs have succeeded in delivering mRNA intranasally, intratracheally, and intramuscularly in preclinical settings. However, intravenous mRNA delivery has been less explored. Only a few NPs have been tested for systemic delivery of mRNA, many of which are formulated with polyethylene glycol (PEG). The incorporation of PEG presents some tradeoffs that must be carefully considered when designing a systemic delivery model. For example, while the addition of PEG may prolong circulation time by preventing early clearance by the mononuclear phagocytic system (MPS), it has also been reported that treating patients with PEGylated drugs can result in hypersensitivity reactions due to anti-PEG antibodies. Thus, it is desirable to have alternative PEG-free delivery methods for mRNA to avoid these adverse effects while preserving the beneficial effects. Our research group developed BAPCs (branched amphiphilic peptide capsules), a peptide-based nanoparticle that resists disruption by chaotropes, proteases, and elevated temperature, thus displaying significant stability and shelf-life. In this study, we demonstrated that similarly to PEG, mRNA shields the BAPC cationic surface to avoid early clearance by the MPS. Multispectral optoacoustic tomography (MSOT) and fluorescence reflectance imaging were imaging techniques used to analyze biodistribution within major MPS organs. Analysis of pro-inflammatory cytokine expression showed that BAPC-mRNA complexes do not cause chronic inflammation. Additionally, BAPCs enhance intracellular delivery of mRNA with negligible cytotoxicity or oxidative stress. These results might pave the way for future therapeutic applications of BAPCs as a delivery platform for systemic mRNA delivery.